A DSGE Model with Partial Euroization: The Case of the Macedonian Economy - Mihai Copaciu; Joana Madjoska; Mite Miteski (Economy, Business and Development: An International Journal (EB&D), 2021)
This paper describes the theoretical structure and estimation results for a DSGE model for the Macedonian economy. Having as benchmark the model of Copaciu et al. (2015), modified to allow for a fixed exchange rate, we are able to match relatively well the volatility observed in the data. Given the monetary policy regime in place, the debt deflation channel is more important relative to the financial accelerator one when compared to the flexible exchange rate case. The lack of balance sheet effects results in no significant differences in terms of net worth evolution across the two types of entrepreneurs when impulse response functions are evaluated. However, the shocks related to the financial sector appear to be especially important for investment, for the domestic interest rate and interest rate spreads, illustrating the relevance of including financial frictions in the model. With the exchange rate not acting as a shock absorber, the external shocks are more relevant for the CPI inflation and the domestic interest rate. The drop in GDP associated with the pandemic mainly reflects the negative innovations to the consumption preference shock and to the permanent technology shock.
Keywords: E0; E3; F0; F4; G0; G1; 330; Bayesian estimation; DSGE model; Financial frictions; Partial euroization; Small open economy